2011
DOI: 10.1016/j.jfms.2010.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Congenital diaphragmatic eventration in two closely related British Shorthair cats

Abstract: Two closely related British Shorthair cats, which died after surgery performed in the dorsal position, were presented for dissection. In both, a thin, flaccid, enlarged transparent tendinous diaphragmatic portion protruded cranially into the thoracic cavity, forming a cupola in which left, right medial and quadrate hepatic lobes were encased in both cats and the stomach in one cat. Microscopically, no muscle fibres were observed in the membrane, but numerous hepatocytes and bile ducts were incorporated in its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…Such material has been used successfully to correct of anatomical defects in animals, as its crystalline molecular structure provides excellent tensile strength [2]. The lesions observed on necropsy and histopathological examination are consistent with those reported by Gombac et al in cats [3], namely, fragile and thin diaphragmatic muscles, with the affected portions protruding into the thoracic cavity and marked muscular atrophy.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Such material has been used successfully to correct of anatomical defects in animals, as its crystalline molecular structure provides excellent tensile strength [2]. The lesions observed on necropsy and histopathological examination are consistent with those reported by Gombac et al in cats [3], namely, fragile and thin diaphragmatic muscles, with the affected portions protruding into the thoracic cavity and marked muscular atrophy.…”
Section: Discussionsupporting
confidence: 72%
“…Dyspnea in animals may be caused by a decrease in pulmonary functional capacity associated with abnormal diaphragm movement [5]. Gombac et al [3] reported a case of two young cats with congenital diaphragmatic eventration that presented with severe dyspnea, cyanosis and apathy. In humans, respiratory distress has been reported in infants with diaphragmatic herniation, in older children and adults, this condition may be asymptomatic [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, true diaphragmatic hernia is characterized as a hernia sac surrounded by serosa, and these unique features are different from those of other types of diaphragmatic hernia. Most previous cases with true diaphragmatic hernia were confused with pulmonary mass or peritoneopericardial diaphragmatic hernia on radiography and confirmed as true diaphragmatic hernia through surgery or necropsy [1][2][3][4][5]. In four cases, positive contrast peritoneography diagnosed true diaphragmatic hernia by revealing incomplete diaphragmatic defects between peritoneal and pleural cavities [6][7][8].…”
Section: Introductionmentioning
confidence: 99%